БЕРДАҚ ШЫҒАРМАЛАРЫНДА «ЖАҚСЫ» ҲӘМ «ЖАМАН» ТҮСИНИКЛЕРИ - Пазылов, А. (SCIENCE and SOCIETY, 2018)
The article contains the information about research works, devoted to the study of literary, philosophical and pedagogical points of view of the poet classic Berdakh, the interest of the world character to Berdakh’s creation and pedagogical ideas in the didactical poetic works.
Keywords: concepts «good» and «bad»; positive and negative qualities of a person; educational meaning; Pedagogy